Conscripted Argentine Youth in Three Military Mobilization Spaces in the 1970s - Di Renzo, Cristian Andrés; Mosiewicki, Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper analyzes the way in which conscripted Argentine youth supported the patriotic ideal in three cases of military mobilization: the impeachment of the de facto President Juan Carlos Onganía (1970), the so called «Operation Independence» (1975) and «Operation Sovereignty» (1978). These three cases, developed conceptions about the effort that the Homeland demanded from youth serving their civil duty by means of compulsory military service. At the same time, in daily life, this conception of war experience was nuanced by the conscripts ́ own understandings of the meaning of duty. This study is based on a methodology that contributes to history of emotions and seeks to understand the cross between efforts to condition the emotional experiences of youth and the formation of counter-discourses and anti-hegemonic spaces. In the same way, the act of giving value to concepts such as «banal nationalism», will enable a debate about different forms in which national identity constituted a national war fervor in three particular moments.